Lamb wave based structural health monitoring using fibre bragg grating-based intrinsic fabry-perot interferometer sensor - Nurazima, Ismail (2023)
The demand for an increase in structural safety and a reduction in structural maintenance costs can be achieved by applying a reliable monitoring system. Such systems are called structural health monitoring (SHM) systems. There are several SHM techniques suitable for engineering structures such as acoustic emission (AE), electromechanical impedance (EMI) or Lamb waves testing. The applications of Lamb waves for SHM systems are highly desirable owing to their advantages compared to other approaches. Lamb waves are elastic waves having dispersive behaviours that propagate in plates and shell-like structures. The detection of damage comes from the interaction of Lamb waves with defects in the structures. These defects triggered reflections and conversions of the Lamb modes. The changes in the Lamb wave signals are extracted to detect the damage in the monitored structure. These interactions are complex. Thus, a higher sensitivity sensor is required to capture the interaction of the Lamb wave for applications in SHM systems. The present work proposed an optical fibre sensor, fibre Bragg grating-based intrinsic Fabry-Perot interferometer (FBG-IFPI) sensor for damage detection using Lamb wave technique. It is a hybrid of the fibre Bragg grating sensor and the Fabry-Perot interferometer sensor. The effect of the variation of optical cavity length, the directional sensitivity, and the response of the sensor towards the strain were evaluated. A positive result was observed from that evaluation. It was found that the sensitivity was higher for the longer optical cavity length. The FBG-IFPI with a 10 mm optical cavity length has an FSR of 83 pm, while FBG-IFPI with a 20 mm optical cavity length has an FSR of 34 pm. A smaller FSR indicates a steeper edge and yields a higher strain on optical power amplification, which presents higher sensitivity and resolution in the sensing. The result shows that the sensitivity enhancement in the longer optical cavity is 2.46 times higher. The FBG-IFPI sensor was at its maximum performance when it was oriented in the radial direction (0°) of the source Lamb wave, which shows an increment of 75% for amplitude detection compared to when it is oriented at the right angle with the radial direction (± 90°). In addition, the sensor performance in strain sensing was improved by identification of the optimum wavelength. This wavelength would maximise the sensitivity of the sensor to small changes in strain. It shows an increment of about 7.4% compared to the strain sensitivity of the single FBG. Other than that, the improvement of the FBG-IFPI sensor can also be observed using the absolute gradient curve, which shows the sensitivity is 7.5 times higher than the FBG sensor. The FBG-IFPI sensor was surface mounted on the intact and damaged plate. The sensor was placed at two different positions, that is, 8 and 23 cm from the actuator, which represent the pulse-echo and pitch-catch methods. For the pulse-echo method, additional wave packets are observed due to the reflection from the defect. Meanwhile, for the pitch-catch method, the observation of the amplitude decrements was 66% compared to the intact plate signal. The characteristics of the Lamb waves during interaction with defects for the two methods were successfully detected by the FBG-IFPI sensor and they were validated by Finite Element Analysis (FEA). For the pulse-echo method using FEA, the finding shows that there is also one additional wave packet that appears after the wave interacts with the defect. The analysis of the pitch-catch method shows about 76% amplitude decrement. These characteristics are the damage features that can be used as an indicator for the structure health status. Thus, the main results of the work presented here are the extracted damage indicator from the measured signal using the proposed sensor. This finding shows the applicability of the proposed sensor in damage detection, which can be utilised as the alternative sensor for SHM applications.